Evaluasi Kesesuaian Lahan Kabupaten Dairi Untuk Tanaman Kopi Robusta (Coffea robusta Lindl.) - Muhammad Nazarul Yanis; Hardy Guchi; Mariani Sembiring (Universitas Sumatera Utara, 2014)
This research purposed to evaluate the suitability of land for cultivation of robusta coffee in Dairiwith altitude at 400 - 1700 m above sea level . This research started from May 2013 to November2013. The research conducted by taking a sample soil based by method free survey grid with detailof survey level and then analyzed on the laboratory and land evaluation performed by the matchingmethod is based on plants needed with properties owned by land on any limiting factors. Theparameters observed in the field are soil depth, drainage, slope, the dangers of erosion, the dangersof flood, the rock surface and laboratory parameters analyzed include physical properties, textureand chemical properties of the soil pH, soil cation exchanges capacity, base saturation, C-organic,and soil salinity. The results showed that the actual land suitability classes for sample 1 is S2rc,nr,sample 2 is S3nr, sample 3 is S2oa,rc,nr,eh, sample 4 is S3nr,eh, sample 5 is S3nr, sample 6 is S3nr,sample 7 is Nrc, sample 8 is S3nr, sample 9 is S3tc,rc,nr, sample 10 is S3tc, sample 11 is S3nr,sample 12 is S3tc,oa,rc,nr, sample 13 is S3tc,nr, sample 14 is S3tc,rc, sample 15 is S3tc,nr,uh, andsample 16 is Nrc. Potential land suitability classes for sample 1 is S2rc, sample 2 is S2rc,nr, sample3 is S2rc, sample 4 is S2rc,nr,eh, sample 5 is S2rc,nr, sample 6 is S3rc,nr, sample 7 is Nrc, sample 8is S2rc,nr, sample 9 is S3tc,rc, sample 10 is S3tc, sample 11 is S2rc,nr, sample 12 is S3tc,rc, sample13 is S3tc, sample 14 is S3tc,rc, sample 15 is S3tc, and sample 16 is Nrc.Keywords : Land Evaluation, Dairi Regency, Robusta Coffe